Role of Phytochemicals in Perturbation of Redox Homeostasis in Cancer - Shreyas Gaikwad; Sanjay K. Srivastava (MDPI AG, 2021)
Over the past few decades, research on reactive oxygen species (ROS) has revealed their critical role in the initiation and progression of cancer by virtue of various transcription factors. At certain threshold values, ROS act as signaling molecules leading to activation of oncogenic pathways. However, if perturbated beyond the threshold values, ROS act in an anti-tumor manner leading to cellular death. ROS mediate cellular death through various programmed cell death (PCD) approaches such as apoptosis, autophagy, ferroptosis, etc. Thus, external stimulation of ROS beyond a threshold is considered a promising therapeutic strategy. Phytochemicals have been widely regarded as favorable therapeutic options in many diseased conditions. Over the past few decades, mechanistic studies on phytochemicals have revealed their effect on ROS homeostasis in cancer. Considering their favorable side effect profile, phytochemicals remain attractive treatment options in cancer. Herein, we review some of the most recent studies performed using phytochemicals and, we further delve into the mechanism of action enacted by individual phytochemicals for PCD in cancer.